It’s All Their Fault? - Clyde Freeman Herreid (American Society for Microbiology, 2010)
Many students fail our introductory science courses and give up on science altogether. How much of this is their fault is debatable. But what is not debatable is that we can improve the situation by using active learning methods. Many faculty claim critical thinking is their highest priority. Their teaching seldom reflects this. They emphasize facts and lecture without context. Most of our students are not going to be scientists, but they are going to be citizens and need to be able to spot inaccuracies when they appear in the media. Case-based and Problem-based Teaching are proven ways to achieve this goal.